DUOLINGO : AN APP TO BOOST STUDENTS' VOCABULARY IN SPEAKING - Meliyuana, Putri; Suryani, Suryani; Dauyah, Ema (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
The purposes of this study are to determine the improvement and perception of students about the use of the Duolingo application as an English learning tool. This research uses quantitative method. The sample of this study was 22 students in IPAS-3 class of the academic year 2023/2024. Data was obtained through the collection of test results and distribution of questionnaires. The test contains one topic about